2015
DOI: 10.1038/srep10641
|View full text |Cite
|
Sign up to set email alerts
|

Novel EPHB4 Receptor Tyrosine Kinase Mutations and Kinomic Pathway Analysis in Lung Cancer

Abstract: Lung cancer outcomes remain poor despite the identification of several potential therapeutic targets. The EPHB4 receptor tyrosine kinase (RTK) has recently emerged as an oncogenic factor in many cancers, including lung cancer. Mutations of EPHB4 in lung cancers have previously been identified, though their significance remains unknown. Here, we report the identification of novel EPHB4 mutations that lead to putative structural alterations as well as increased cellular proliferation and motility. We also conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 59 publications
(53 reference statements)
0
25
0
Order By: Relevance
“…Enhanced apoptosis is one of the key anti-tumor responses mediated by EphB4 targeting and radiation325262728. In caspase-3/7 assay, we observed a significant increase in apoptosis (~28%) in Fadu cells transfected with EphB4-siRNA and 4 Gy dose of radiation compared to radiation alone at 96 h (Fig.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Enhanced apoptosis is one of the key anti-tumor responses mediated by EphB4 targeting and radiation325262728. In caspase-3/7 assay, we observed a significant increase in apoptosis (~28%) in Fadu cells transfected with EphB4-siRNA and 4 Gy dose of radiation compared to radiation alone at 96 h (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…Ferguson et al . have shown that in lung carcinoma cells, EphB4 knockdown affects apoptosis by altering the expression of the JAK-STAT family of proteins25. Another study by Pradeep et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…EPHB4 plays a crucial role in cardiovascular development and regulates vascularization in cancer‐promoting angiogenesis, tumour growth and metastasis 41 . Several EPHB4 mutations have previously been identified in solid and haematological tumour specimens 42‐44 . Many other variants in other types of tumours and cell lines have been identified and catalogued in “The Cancer Genome Atlas project” 24 .…”
Section: Discussionmentioning
confidence: 99%
“…15,16 EPHB4 mutations have been reported in some epithelial cancers, such as lung cancer, whereas EPHB4 gene amplification occurs in nearly one-third of head and neck cancers. 17,18 Furthermore, we have shown that EGFR activation, loss of PTEN, or Kras G12D activating mutations induce EPHB4 (Xi et al, 8 Masood et al, 17 Huang and Li, 19 and P.S.G., unpublished data). Despite this wealth of data describing EPHB4/ephrinB2 in cancer, very little has been published about this pathway in leukemia.…”
Section: Introductionmentioning
confidence: 99%